Answer:
[tex]a_n=7 \cdot (-3)^{n-1}[/tex]
Step-by-step explanation:
The explicit form for a geometric sequence is [tex]a_n=a_1 \cdot r^{n-1}[/tex] where [tex]a_1[/tex] is the first term and [tex]r[/tex] is the common ratio.
We have the following given:
[tex]a_2=-21[/tex]
[tex]a_5=567[/tex].
We also know that [tex]a_2=a_1 \cdot r[/tex] while [tex]a_5=a_1 \cdot r_4[/tex].
So if we do 5th term divided by second term we get:
[tex]\frac{a_1 \cdot r_4}{a_1 \cdot r}=\frac{567}{-21}[/tex]
Simplifying both sides:
[tex]r^3=-27[/tex]
Cube root both sides:
[tex]r=-3[/tex]
The common ratio, r, is -3.
Now we need to find the first term.
That shouldn't be too hard here since we know the second term which is -21.
We know that first term times the common ratio will give us the second term.
So we are solving the equation:
[tex]a_1 \cdot r=a_2[/tex].
[tex]a_1 \cdot (-3)=-21[/tex]
Dividing both sides by -3 gives us [tex]a_1=7[/tex].
So the equation is in it's explicit form is:
[tex]a_n=7 \cdot (-3)^{n-1}[/tex]
Check it!
Plugging in 2 should gives us a result of -21.
[tex]a_2=7 \cdot (-3)^{2-1}[/tex]
[tex]a_2=7 \cdot (-3)^1[/tex]
[tex]a_2=7 \cdot (-3)[/tex]
[tex]a_2=-21[/tex]
That checks out!
Plugging in 5 should give us a result of 567.
[tex]a_5=7 \cdot (-3)^{5-1}[/tex]
[tex]a_5=7 \cdot (-3)^4[/tex]
[tex]a_5=7 \cdot 81[/tex]
[tex]a_5=567[/tex]
The checks out!
Our equation works!